Increasing light coupling in a photovoltaic film by tuning nanoparticle shape with substrate surface energy - Kataria, Devika; Krishnamoorthy, Kothandam; Iyer, S. Sundar Kumar (Materials Research Express, 2017)
Tuning metal nanoparticle (MNP) contact angle on the surface it is formed can help maximise the useful optical coupling in photovoltaic films by localized surface plasmon (LSP) resonance-opening up the possibility of building improved photovoltaic cells. In this work experimental demonstration of optical absorption increase in copper phthalocyanine (CuPc) films by tuning silver MNP shape by changing its contact angles with substrate has been reported. Thin films of poly3,4 ethylenedioxythiophene: sodium dodecycl sulphate (PEDOT: SDS) with different surface energies were formed on indium tin oxide (ITO) coated glass by electro-deposition. Silver MNPs thermally evaporated directly on ozonised ITO as well as on the PEDOT: SDS films showed contact angles ranging from 60 degrees to 125 degrees. The CuPc layer was deposited on top of the MNPs. For the samples studied, best optical absorption in the CuPc layer was for a contact angle of 110 degrees.